ANALISIS KENDALA DAN STRATEGI PENGEMBANGAN USAHA RUMPUT LAUT DI KABUPATEN KONAWE SELATAN - La Hadifa; La Rianda; La Sara (Universitas Halu Oleo, 2017)
This study aimed to determine the productivity of seaweed cultivation, marketing channel and margins, any constraints and alternative steps in the development of seaweed business strategy in Konawe Selatan Regency. Data collection methods used were observation, interviews, and documentation. Data were analyzed using qualitative and quantitative descriptive techniques, and the Analytical Hierarchy Process (AHP) analysis. The results showed that the productivity of seaweed cultivation of dried products reached 8,559.988 kg/ha and productivity of wet products reaches 18,442.072 kg/ha. The absolute marketing margin on marketing channel I and channel II were Rp1,250 (14.71%) and Rp 750 (8.57%), respectively. Based on the results of the AHP analysis known that the sequency of Relative Priority (RP) at the level of subsystems are the following: supporting subsystem components; marketing subsystem; production facilities subsystem; the processing subsystem; and production subsystems. The AHP analysis results known that the order of priority constraints consists of the institutional constraints; capital; human resources; selling price; productivity; seeds; and technology of postharvest processing; while the order of priority strategies comprises of strengthening strategy of institutional role; development of farmers capacity; strengthening of capital; seed breeding; and procurement of postharvest processing technology. Keywords: constraint; strateg;, productivity; income; AHP